A divulgação científica na formação inicial de professores de química - Dapieve, Diane Ferreira da Silva (2016)
Various authors have discussed the importance of using science dissemination (SD) to teach sciences, and have emphasized the contributions of this didactic resource in teaching and learning processes and in the construction of scientific knowledge. However, this resource is not used very often to teach sciences, especially chemistry. Thus, we highlight the importance of promoting debate about the resource, as well as its development in teaching situations during initial education. This study investigated how a group of university chemistry students understood SD and its contribution as a didactic resource to chemistry teaching. Thirteen (13) chemistry students from a public university located in western Paraná state (Brazil) participated. All responded to questionnaires and four (4) took part in a semi-structured interview. The data was analyzed in accordance with Bardin content analysis and compared to the theoretical reference on which the research was based. Regarding the results, we highlight some of the categories that emerged from the responses of the participants: understanding of SD, SD methods in initial education, possibilities and advantages of SD in teaching, and contribution of SD methods to teacher education. In respect of understanding about SD, the students understood SD as the dissemination of knowledge to the general public, and realized its importance in the expansion of societal knowledge about research and scientific and technological advances. We show that the students used SD as a didactic resource in some disciplines, with the pedagogical disciplines using SD the most in teaching situations. Used as possibilities and advantages, the students argued that SD can favor interest in lessons, reading, and a break with a linear view of science. We can infer that SD was developed significantly in the initial education of the students, so much so that several of them used SD as a didactic resource in their internships.